Medical Errors Cause Harm in Veterinary Hospitals - Wallis, Jessica; Fletcher, Daniel; Bentley, Adrienne; Ludders, John (Frontiers in Veterinary Science, 2019)
Medical errors are a leading cause of mortality in human medicine. In contrast, errors in veterinary medicine are rarely discussed, and there is little known about their nature and frequency. This study aimed to evaluate the type and severity of medical errors reported in three veterinary hospitals. The voluntary online incident reporting systems of a small animal teaching hospital, large animal teaching hospital, and small animal multi-specialty practice were reviewed. Reports were included if they were entered between February 2015 and March 2018, and involved an incident pertaining to patient safety. The reporting systems classified errors into the following categories: drug, iatrogenic, system, communication, lab, oversight, staff, or equipment errors. In addition, all incidents were classified as resulting in either a near miss, harmless hit, adverse incident, or unsafe condition. Adverse incidents were further evaluated retrospectively for error severity. A total of 560 incident reports were included for analysis. Drug errors were the most frequently reported in all three hospitals, followed by failures of communication. Errors most commonly reached patients without causing harm (45%); however, 15% of all incidents resulted in patient harm. Eight percent of patients harmed suffered permanent morbidity or death. A higher proportion of adverse incidents were reported in the small animal teaching hospital than in the other two practice settings. This study demonstrates that medical errors have a substantial impact on veterinary patients. Establishing that drug and communication errors are most frequent in a variety of hospitals is the first step towards interventions to improve patient safety and outcomes in veterinary medicine.